Strategi Pengelolan Wisata Pedesaan Berbasis Topografi Alam Perbukitan di Desa Pule Kec. Pule Kabupaten Trenggalek - Nazlia; Ubaidillah (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
Pule village topography is a hilly area that has economic potential if it is managed well. The functions of it are as water absorption and earthquake defense, besides that the hilly area also can be as ecotourism for the alternative strategy of economic enhancement and for ecosystem education. This research-based service aims to empower the community economy and apply the education that is integrated with nature through participatory method related to the goals achieved. The first result, officially opened the ecotourism with the views of Kekep Hills. The second, the forming of community-based tourism (Pokdarwis) as the management of ecotourism. The third, the education that is integrated of nature becomes the educational and fun media. It was created by using ecotourism pattern to grow the awareness of conservation for childhood